ANALISIS KEBERLANJUTAN EKONOMI MASYARAKAT LOKAL DALAM MENGHADAPI DOMINASI INVESTASI PARIWISATA DI KAWASAN NUSA DUA KABUPATEN BADUNG - Putu Ratna Windusara Putri; Fahmi Tanjung; I Made Wisnu Wardana; I Made Sujana (Nusantara Hasana Journal, 2024)
The Rapid Growth Of Tourism Investment In The Nusa Dua Area Has Significantly Contributed To Regional Economic Development. However, The Dominance Of Large-Scale Tourism Investments Also Presents Challenges To The Economic Sustainability Of Local Communities. This Study Aims To Analyze The Sustainability Of Local Community Economies In Facing Tourism Investment Domination In Nusa Dua, Badung Regency. The Research Employed A Descriptive Qualitative Approach Supported By Quantitative Data Collected Through Surveys, Interviews, Observations, And Documentation. The Respondents Consisted Of 50 Local Community Members Engaged In Tourism-Related Economic Activities. The Findings Indicate That Tourism Investment Has Generated Positive Impacts Through Employment Opportunities, Increased Income, And Business Expansion. Nevertheless, Challenges Remain Regarding Unequal Access To Economic Opportunities, Increasing Competition, And The Limited Capacity Of Local Businesses To Compete With Larger Investors. Strengthening Local Entrepreneurship, Improving Human Resource Quality, And Implementing Inclusive Tourism Policies Are Essential Strategies To Maintain Economic Sustainability. The Study Concludes That Collaboration Among Government, Investors, And Local Communities Is Crucial For Achieving Sustainable And Equitable Tourism Development.